28
Аноним
Математика
09 марта 12:45

Упростить выражение 1)(a-5)^2+9(a-2) 2)2(b-3)^2+12b 3)(a+6)^2+(3a-1)(3a+1) 4)(b+4)^2+(2b-5)(2b+5)

Ответ или решение1

Орлов Ростислав

чтобы упростить данные выражения, нам необходимо вспомнить формулы. 

(a − b)^= a^− 2ab + b^2;

(a + b)^2 = a^+ 2ab + b^2;

а^2 - b^2 = (a + b) * (a - b).

1) (a - 5)^2 + 9( a - 2) = a^2 - 10a + 25 + 9a - 18 = a^2 - a + 7;

2) 2 * (b - 3)^2 + 12b = 2 * (b^2 - 6b + 9) + 12b = 2b^2 - 12b + 18 + 12b = 2b^2 + 18 =           = 2 * (b^2 + 9);

3) (a + 6)^2 + (3a - 1) * (3a + 1) = a^2 + 12a + 36 + 9a^2 - 1 = 10a^2 + 12a + 35;

4) (b + 4)^2 + (2b - 5) * (2b + 5) = b^2 + 8b + 16 + 4b^2 -25 = 5b^2 + 8b - 9.

0 / 10000
ВходРегистрация

Вход

или

Регистрация